Effect of regional cooperation on outcomes from ruptured abdominal aortic aneurysm. Issue 7 (22nd April 2014) - van Beek, S C; Reimerink, J J; Vahl, A C; Wisselink, W; Reekers, J A; van Geloven, N; Legemate, D A; Balm, R
Abstract: Background: Care for patients with a ruptured abdominal aortic aneurysm (rAAA) in the Amsterdam ambulance region (The Netherlands) was concentrated into vascular centres with a 24-h full emergency vascular service in cooperation with seven referring regional hospitals. Previous population-based survival after rAAA in the Netherlands was 46 (95 per cent confidence interval (c.i.) 43 to 49) per cent. It was hypothesized that regional cooperation would improve survival. Methods: This was a prospective observational cohort study carried out simultaneously with the Amsterdam Acute Aneurysm Trial. Consecutive patients with an rAAA between 2004 and 2011 in all ten hospitals in the Amsterdam region were included. The primary outcome was 30-day survival after admission. Multivariable logistic regression, including age, sex, co-morbidity, intervention (endovascular or open repair), preoperative systolic blood pressure, cardiopulmonary resuscitation and year of intervention, was used to assess the influence of hospital setting on survival. Results: Of 453 patients with rAAA from the Amsterdam ambulance region, 61 did not undergo intervention; 352 patients were treated surgically at a vascular centre and 40 at a referring hospital. The regional survival rate was 58·5 (95 per cent c.i. 53·9 to 62·9) per cent (265 of 453). After multivariable adjustment, patients treated at a vascular centre had a higher survival rate than patients treated surgically at a referring hospital (adjusted odds ratio 3·18, 95 per cent c.i. 1·43 to 7·04). Conclusion: After regional cooperation, overall survival of patients with an rAAA improved. Most patients were treated in a vascular centre and in these patients survival rates were optimal. Abstract : Centralization works